Commodity Prices As a Leading Indicator of Inflation. (IMF Working Papers; Working Paper, 1988)
Commodity prices may be a leading indicator of inflation, because of the relative importance of flexible auction markets for the determination of these prices. Empirical tests using data for the large industrial countries as a group suggest that changes in commodity prices tend to lead those in consumer prices, and that the inclusion of commodity prices significantly improves the fit of regressions of a multi-country consumer price index. However, there does not appear to be a reliable long-run relationship between the level of commodity prices and the level of consumer prices.